2016
DOI: 10.1016/j.bbrep.2016.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Mice with low levels of Shc proteins display reduced glycolytic and increased gluconeogenic activities in liver

Abstract: Shc proteins play a role in energy metabolism through interaction with the insulin receptor. The aim of this study was to determine whether Shc proteins influence liver glycolysis and gluconeogenesis under both fed and fasted states. Decreased glycolytic and increased gluconeogenic and transamination enzyme activities were observed in ShcKO versus WT mice. Levels of key regulatory metabolites, such as fructose-2,6-bisphosphate, matched the activity of metabolic pathways. Protein levels of glycolytic and glucon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Decreased levels of Shc proteins have been shown to produce concerted shifts in the activities of enzymes of intermediary metabolism towards an increase in capacity for fatty acid oxidation and a decrease in capacity for glycolysis , . These changes are most pronounced with fasting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased levels of Shc proteins have been shown to produce concerted shifts in the activities of enzymes of intermediary metabolism towards an increase in capacity for fatty acid oxidation and a decrease in capacity for glycolysis , . These changes are most pronounced with fasting.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] The activities of regulatory enzymes of glycolysis (gluckinase/hexokinase, phosphofructokinase-1, and pyruvate kinase) were significantly decreased in liver and skeletal muscle of ShcKO compared to WT mice with fasting and 3 hours following feeding. 9,10 ShcKO mice also showed a significant increase in the activities of mitochondrial β-oxidation enzymes, although this change in enzyme activities only occurred under fasting conditions. 8 The results of these studies suggest that Shc proteins may play a role in fuel selection.…”
Section: Introductionmentioning
confidence: 99%
“…However, results indicate that there are substantial changes in energy metabolism in ShcKO mice in the fasted state . In particular, enzyme activity measurements in skeletal muscle and liver indicate a shift in metabolism towards increased capacity for fatty acid oxidation, ketogenesis, ketone body catabolism, gluconeogenesis, and amino acid catabolism, while capacity for glycolysis is decreased in ShcKO compared to WT mice under fasting conditions (Hagopian et al, 2016). These changes in enzyme activities mirror those observed in animals under caloric restriction (CR) conditions Stern et al, 2012a).…”
Section: Shc Proteinsmentioning
confidence: 84%
“…In general, the approaches associate decreased Shc levels with changes in the mitochondrial generation of ATP, regulation of mtDNA replication, energy expenditure and protection against oxidative stress in main body tissues following consumption of a HFD. It is important to note that the p66Shc knockout mice used by investigators have recently been shown to have low levels of all Shc isoforms in many tissues (Hagopian et al, 2016;. Thus, it is difficult to determine if observed changes are truly due to p66Shc or due to one of the other Shc isoforms.…”
Section: Shc Proteinsmentioning
confidence: 99%
See 1 more Smart Citation